Controle postural dinâmico e risco de quedas em idosas fisicamente ativas - Amaral, Taís Fernandes (2021)
With each passing year, the number of elderly people grows, and this generates significant changes associated with sociocultural changes, physiological changes and skeletal muscle, as these changes bring damage to bodily systems that culminate in decreased mobility, postural control and balance, potential risks for falls. Falls are the main cause of unintentional death and injury among the elderly, considered the most common accident in this age group. The regular practice of physical activity has been shown to be beneficial and helps to minimize the impacts caused by advancing age, acting on structural and functional changes that make the individual vulnerable to falls. The aim of this study was to compare dynamic postural control and the risk of falls in physically active elderly women, as falls usually occur in a dynamic situation. The research consists of a documental study from the database of the original research of a descriptive, observational, transversal type with a quantitative approach. Forty elderly women, aged between 60 and 83 years (66.3±5.6), physically active, evaluated by the International Physical Activity Questionnaire (IPAQ) were selected from the database. The participants in this study were recruited from groups of elderly women involved in physical activities linked to the Integrated Center for Studies and Support for the Elderly (NIEATI) of a city in the interior of Rio Grande do Sul. The risk of falls was assessed using the Timed Up and Go ( TUG) dividing the elderly women into two groups: without risk (n=17; 64.6 ± 4.3 years) and at risk of falls (n=23; 67.6 ± 6.1 years) and for analysis purposes for In this research, due to sample limitations, elderly women were divided into two groups: without risk of falls (n=17) and at risk of falls (n=23). falls and high risk of falls classified by the TUG. To assess the oscillation of the Center of Pressure (COP) displacement, the Force Platform was used, through the squatting movement, chosen because it is a movement commonly used by most individuals for activities of daily living. Comparisons between groups of parametric continuous variables were performed using the two-tailed independent Student's T test and, for non-parametric ones, the Mann Whitney U Test was used. For sociodemographic comparisons, between groups, of categorical variables, the Chi-square test was used. The significance level adopted for all analyzes was (p<0.05). As for the characterization of the sample, there was a significant difference only in the ethnicity variable (p=0.004). There was no significant difference between the groups in the variables of displacement of the center of pressure and risk of falls, except for the variable amplitude of mean lateral displacement of COPml (p=0.044), where the group at risk of falls had the lowest oscillation. It was concluded that physically active elderly women, classified by TUG as at risk and without risk of falls, presented similar behavior in terms of dynamic postural control during the squat task.